Perspectives from farmers: What is the future of food for the world? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Farmers from India, Peru and Kenya share their climate change stories, and tell us what they want to see in the future. Filmed at the UN Climate Change conference COP20 in Lima, December 2014. Find out more at https://ccafs.cgiar.org Agricultores de la India, PerÁº y Kenia comparten sus historias relacionadas con el cambio climático, y nos cuentan cómo ven el future. Hablamos con ellos durante la conferencia de cambio climático de la ONU COP20 en Lima, diciembre de 2014.